The Prevalence of High Risk Human Papilloma Viral Infection and Abnormal Cervical Cytology in Faculties of Medicine and Nursing, Chiang Mai University Population - Wittawat Choeypan; Prapaporn Suprasert; Kornkanok Sukpan; Jongkolnee Settakorn (The Royal Thai College of Obstetricians and Gynaecologists, 2014)
Objective:To evaluate the prevalence of high risk HPV infection and abnormal liquid based cytology (LBC) in healthcare population of Faculty of Medicine and Nursing, Chiang Mai University.Material and Method:Healthcare population who aged ≥ 30 years and no history of preinvasive or invasive cervical cancer from both faculties were invited. LBC was done by collecting a specimen into Thin Prep Pap test solution and Cobas® 4800 was used for high risk HPV testing. The persons with abnormal cytology and /or HPV type 16/18 positive were referred for colposcopy. Results: Between September, 2012 and April, 2013, 261 persons joined this project. Sixteen persons (6.1%) revealed abnormal cytology that consisted of ASCUS ten persons, LSIL four persons and HSIL two persons. Positive HPV test were also found in 16 persons (6.1%). Twelve persons (4.6%) showed positive only in the cytology or HPV tests while four persons tested positive in both methods. HPV type 16 was detected in one person and HPV type 18 was detected in two persons. With 17 persons who were referred for colposcopy, the colposcopic-directed biopsy and conization were done in seven and three persons, respectively. Of these persons, the histology showed chronic cervicitis in three persons, LSIL in four persons and HSIL in three persons. One HSIL person revealed only HPV type 16 positive without abnormal cytology.Conclusion: The prevalence of high risk HPV infection and abnormal cytology seems to be minimal in healthcare population. Infected HPV type 16/18 persons should be referred for colposcopy even with normal cytology.